An evolutionary analysis on the effect of government policies on electric vehicle diffusion in complex network. (June 2019) - Li, Jingjing; Jiao, Jianling; Tang, Yunshu
Abstract: In response to severe energy and environmental challenges, electric vehicles (EVs) have been thoroughly considered by governments. Although China has become the largest EV market, currently the limitations of EVs and decreasing subsidies have led to a challenging future. To promote EV diffusion, we use a complex network evolutionary game method to explore the dynamic impacts of government policies on EV diffusion in different scale networks. The results show that with the increase in manufacturers in the network, the degree of EV diffusion increases accordingly at the same government policy level. In the present network scale of manufacturers, on the supply side, the effects of tax and subsidy policies can respectively promote EV diffusion to 0.82 and 0.86. Fuel vehicle (FV) license plate restrictions and consumer purchase subsidies are effective policies on the demand side, which both can promote EV diffusion to 0.84. Compared with consumer purchase subsidies, production subsidies for manufacturers have better effects on EV diffusion. Neither the tax and subsidy policies nor the FV license plate restriction and EV purchase subsidy policies can realize full EV diffusion. Finally, combined with the current status of China's automobile industry, the corresponding policy recommendations for different periods are given. Highlights: A complex network evolutionary game method is used to explore the dynamic impacts. We consider the interactions among government, enterprises and consumers. Production subsidies have better effects on EV diffusion than purchase subsidies. None of these policies can realize the full diffusion of EV. This study can bring important insights into EV policy making in China.